The effect of board of directors and sharia supervisory board on zakat funds at Islamic banks in indonesia - Ataina Hudayati; Ihsan Muhamad; Marfuah Marfuah (Cogent Business & Management, 2023)
AbstractThe purpose of this study was to analyze the impact of corporate governance on the distribution of zakat funds by Islamic banks in Indonesia. The study focused on two elements of governance: the characteristics of the board of directors (BOD) and the sharia supervisory board (SSB). Data were extracted from the annual reports of Islamic banks in Indonesia from 2011 to 2020 and analyzed using panel data regression in EViews. The results showed that the size and remuneration of the BOD and the size of the SSB had a significant positive effect on zakat funds, while the reputation of the SSB had no effect. This study contributes to the literature on the role of governance in improving the performance of Islamic banks by providing empirical evidence of the link between governance and increased zakat funds. While previous research has primarily focused on the role of governance in financial performance, this study highlights the importance of governance in the context of social responsibility. The practical implication of this study is that Islamic banks wishing to improve social performance, namely zakat funds, should consider designing a large BOD and large SSB structure, while also considering increasing BOD remuneration.